Species composition, diversity and traditional uses of plants in homegardens in Kampung Masjid Ijok, Perak, Malaysia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ramli MR, Milow P, Malek S. 2021. Species composition, diversity and traditional uses of plants in homegardens in Kampung Masjid Ijok, Perak, Malaysia. Biodiversitas 22: 1902-1911. The aim of present study was to analyze the status, plant diversity and their utilization in homegardens of Kampung Masjid Ijok, Perak, Malaysia. Forty homegardens were selected for detailed study: 9 were large (>1,500m2), 11 medium (901m2 to 1500m2) and 20 small (
Keywords: Homegardens, Kampung Masjid Ijok, Perak, plants diversity